Preparation of hierarchical CMoS2@C sandwiched hollow spheres for lithium ion batteries - Li, Zhenyou; Ottmann, Alexander; Sun, Qing; Meyer, Hans-Peter; Vaynzof, Yana; Klingeler, Rüdiger (Journal of materials chemistry. A, Materials for energy and sustainability, 2017)
Hierarchical CMoS2@C hollow spheres with active MoS2 nanosheets being sandwiched by carbon layers have been produced using a modified template method. The process applies polydopamine (PDA) layers that inhibit morphological changes of the template, enforcing the hollow microsphere structure. In addition, PDA forms complexes with the Mo precursor, leading to the in situ growth of MoS2 on its surface and preventing the nanosheets from agglomeration. It also supplies the carbon that finally sandwiches the 100-150 nm thin MoS2 spheres. The resulting hierarchically structured material provides a stable microstructure, where carbon layers strongly linked to MoS2 offer efficient pathways for electron and ion transfer, and concomitantly buffer the volume changes inevitably appearing during the charge-discharge process. Carbon-sandwiched MoS2-based electrodes exhibit high specific capacity of approximately 900 mA h g−1 after 50 cycles at 0.1C, excellent cycling stability up to 200 cycles, and superior rate performance. The versatile synthesis method reported here offers a general route to design hollow sandwich structures with a variety of different active materials.